2011
DOI: 10.1111/j.1365-2486.2011.02600.x
|View full text |Cite
|
Sign up to set email alerts
|

Methyl chloride isotopic signatures from Irish forest soils and a comparison between abiotic and biogenic methyl halide soil fluxes

Abstract: Forest soils demonstrate in a microcosm the difficulties that are faced in quantifying methyl halide budgets. Carbon isotopic analyses have been proposed as a potential tool to address these concerns and in this study we have measured significant enrichment of the methyl chloride 13C/12C isotopic ratio (from -40.2 +/- 0.8 parts per thousand to -33.4 +/- 7.4 parts per thousand) after 9 min chamber emplacement on local Irish forest soils. This enrichment occurred independent of direction of methyl chloride fluxe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 56 publications
(177 reference statements)
0
30
0
Order By: Relevance
“…The impact of archaea on methyl halide cycling is not yet established and they may play a role in either methyl halide production or consumption within soils and snowpacks. In temperate forest soils, with an estimated 0.1 billion microbial cells per cubic centimetre [47], methyl bromide is reported to be consumed at a rate of 5 mg m 22 d 21 [41]. If we assume that the density of microbial cells in the snowpack is approximately 50 000 cc 21 [48], then we would expect the microbial consumption rate for methyl bromide in the snowpack to be roughly equal to 2.5 ng m 22 d 21 , assuming all else to be equal.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The impact of archaea on methyl halide cycling is not yet established and they may play a role in either methyl halide production or consumption within soils and snowpacks. In temperate forest soils, with an estimated 0.1 billion microbial cells per cubic centimetre [47], methyl bromide is reported to be consumed at a rate of 5 mg m 22 d 21 [41]. If we assume that the density of microbial cells in the snowpack is approximately 50 000 cc 21 [48], then we would expect the microbial consumption rate for methyl bromide in the snowpack to be roughly equal to 2.5 ng m 22 d 21 , assuming all else to be equal.…”
Section: Discussionmentioning
confidence: 99%
“…Methyl bromide and methyl chloride are consumed by bacteria in soils [13,41]. Fungal production may play a role in net fluxes from terrestrial surfaces [8,9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…() for a more detailed treatment of stable isotope fractionation). Stable carbon isotope signatures (ratio of 13 C/ 12 C or δ 13 C values) of chloromethane sources were determined for forest soils (Redeker and Kalin ), plants (Harper et al. ; Keppler et al.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of compound-specific isotope analysis and CH 3 Cl flux measurement has the potential to better constrain the atmospheric CH 3 Cl budget (Keppler et al, 2005;Saito and Yokouchi, 2008). Several studies have determined the stable carbon isotope signatures (d 13 C values) for CH 3 Cl in the atmosphere (Thompson et al, 2002); of its sources in forest soils (Redeker and Kalin, 2012), plants Keppler et al, 2004), fungi , and from biomass burning (Czapiewski et al, 2002); and of its sinks, including methylotrophic CH 3 Cl-degrading bacteria (Miller et al, 2001;Nadalig et al, 2013Nadalig et al, , 2014. Bacterial degradation of CH 3 Cl has been demonstrated in soils (Miller et al, 2004), but modeling studies (Keppler et al, 2005) have suggested that the microbial soil sink for the global atmospheric CH 3 Cl budget might be larger than originally estimated (Montzka and Fraser, 2003).…”
mentioning
confidence: 99%